A remark on Gwinner's existence theorem on variational inequality problem. (15th October 2000) - Vetrivel, V.; Nanda, S.
Abstract : Gwinner (1981) proved an existence theorem for a variational inequality problem involving an upper semicontinuous multifunction with compact convex values. The aim of this paper is to solve this problem for a multifunction with open inverse values.